Prior surgical intervention of the bone; useful finding for the examination of the skeletal remains (Bangladesh Journal of Medical Science, 2010)
In general, personal identification is an important part of forensic practice. Evidence of prior surgery in a skeletonized remains is a useful findings for personal identification. Here we describe two cases where bone scarring shows evidence of prior surgery, and how these findings become useful information for identification of the victims. Key Words: personal identification; skeletal remains; surgical intervention DOI: 10.3329/bjms.v9i2.5658Bangladesh Journal of Medical Science Vol.09 No.2 Apr 2010 pp.101-102